TOLONG-MENOLONG DALAM PENYELENGARAAN PESTA PERNIKAHAN PADA MASYARAKAT BUGIS DI DESA MADELLO KABUPATEN BARRU SULAWESI SELATAN - Mahmud Tang (Al-Qalam, 2009)
In this article I try to describe the activitity of helping each other in thecelebration of wedding party at Buginese society in Madello village Barruregency South Sulawesi. The principal of helping each other which I observedwas in the form of giving service, goods, and money to the parents ofbridegroom and bride. These activities of helping each other are based onthe principle of reciprocity from customary law and religious law. It seemsthat the moslem were earlier practiced these principle tfian the publish ofMalinowski's finding in Trobriand Island (1926). In my assumption, theactivity of helping each other at the Buginese wedding will exist in thefuture as long as they obey to their customary law and religious law.